Intranuclear Crosstalk between Extracellular Regulated Kinase1/2 and Signal Transducer and Activator of Transcription 3 Regulates JEG-3 Choriocarcinoma Cell Invasion and Proliferation. (30th October 2013) - Morales-Prieto, Diana M.; Ospina-Prieto, Stephanie; Chaiwangyen, Wittaya; Weber, Maja; Hölters, Sebastian; Schleussner, Ekkehard; Fitzgerald, Justine S.; Markert, Udo R.
Abstract : Invasiveness of trophoblast and choriocarcinoma cells is in part mediated via leukemia inhibitory factor- (LIF-) induced activation of signal transducer and activator of transcription 3 (STAT3). The regulation of STAT3 phosphorylation at its ser727 binding site, possible crosstalk with intracellular MAPK signaling, and their functional implications are the object of the present investigation. JEG-3 choriocarcinoma cells were cultured in presence/absence of LIF and the specific ERK1/2 inhibitor (U0126). Phosphorylation of signaling molecules (p-STAT3 (ser727 and tyr705) and p-ERK1/2 (thr 202/tyr 204)) was assessed per Western blot. Immunocytochemistry confirmed results, but also pinpointed the location of phosphorylated signaling molecules. STAT3 DNA-binding capacity was studied with a colorimetric ELISA-based assay. Cell viability and invasion capability were assessed by MTS and Matrigel assays. Our results demonstrate that LIF-induced phosphorylation of STAT3 (tyr705 and ser727) is significantly increased after blocking ERK1/2. STAT3 DNA-binding capacity and cell invasiveness are enhanced after LIF stimulation and ERK1/2 blockage. In contrast, proliferation is enhanced by LIF but reduced after ERK1/2 inhibition. The findings herein show that blocking ERK1/2 increases LIF-induced STAT3 phosphorylation and STAT3 DNA-binding capacity by an intranuclear crosstalk, which leads to enhanced invasiveness and reduced proliferation.